SECURITIES ACCOUNT OPENING PADA PT. PHINTRACO SEKURITAS CABANG SURABAYA - Rachma Agustina; Supriyatna (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
The process of involving investors to participate in the capital market requires a form of complete information relating to the status of investors/potential investors, both internally and externally to the company, which allows accuracy and precision to be obtained in an effort to anticipate the risks of investing in the capital market. PT. Phintraco Sekuritas, which in this case is a securities broker, requires several documents to open a client's securities account. The implementation of this service is carried out to guide the mechanism for opening a securities account at PT. Phintraco Sekuritas Surabaya Branch. The method in this activity is carried out by conducting an in-depth study of the mechanism for opening a securities account based on facts. Furthermore, providing assistance and guidance to each investor who intends to open a securities account. The results of the activity show that the opening of stock accounts is divided into 2, namely conventional and sharia, while the documents required for opening include administrative documents in the form of e-KTP, Student Identity Card (for those who are students), 10,000 stamp duty and NPWP. The next requirement that must be completed is the initial account balance of 100,000 which will be sent to the customer's RDN account.